The complete chloroplast genome sequences of monotypic genus Pseudogalium, and comparative analyses with its relative genera - Wei Yu; Xiao-Juan Li; Zhen Lv; Li-E Yang; De-Li Peng (BMC Genomics)
Abstract Background Pseudogalium is a new monotypic genus with two subspecies in China and one in Japan, which holds a distinctive phylogenetic position and ecological significance within the tribe Rubieae. Chloroplast genomes contain abundant information for resolving phylogenetic relationships. To investigate the phylogenetics of P. paradoxum and its related genera, we first sequenced, assembled, and annotated the chloroplast genome of two subspecies of P. paradoxum in China and reconstructed the phylogenetic trees. Due to the lack of samples of P. paradoxum subsp. franchetianum from Japan, this study only analyzed and discussed P. paradoxum subsp. paradoxum and P. paradoxum subsp. duthiei. Results This study had shown that the complete chloroplast genomes of Pseudogalium ranged from 153,093 bp to 153,333 bp in length with 130 genes in total, all of which had typical circular structures consisting of a large single-copy region, a small single-copy region and a pair of inverted repeat regions. The comparative analysis showed that the chloroplast genome of P. paradoxum was conserved in the inverted repeat regions. Additionally, we identified 60 dispersed repeat sequences, 61–63 simple sequence repeats, and 30 codons within the 82 protein-coding genes that exhibited RSCU values greater than one. Furthermore, we detected highly divergent regions that hold potential as new DNA barcodes for species identification. Compared with Pseudogalium, the gene number, gene length, and GC content in the chloroplast genomes of Galium and Rubia exhibited differential characteristics, and the dispersed repeat sequences and SSRs in Galium and Rubia were significantly different. Phylogenetic analysis based on the whole chloroplast genomes showed that Pseudogalium can be treated as a new genus, with P. paradoxum subsp. paradoxum and P. paradoxum subsp. duthiei considered as two distinct subspecies of P. paradoxum. Conclusions The complete chloroplast genomes of P. paradoxum were first reported in this study, which provided a new insight into phylogeny and taxonomy of this genus. Phylogenetic analyses strongly supported the following proposals: (1) P. paradoxum can be isolated as a genus closely related to Galium; (2) P. paradoxum subsp. paradoxum and P. paradoxum subsp. duthiei form distinct clades, both of which can be considered as subspecies of P. paradoxum.